Participative Leadership and Work Culture in Resource-Constrained Vocational High Schools - Vivi Mamoribo; Yulius Mataputun; Juliana Waromi; Indah S. Budiarti; Ida M. Hutabarat (Acitya Wisesa: Journal of Multidisciplinary Research, 2026)
This study examines the participative leadership of school principals in building organizational work culture at a vocational high school in a peripheral region. The research provides empirical contributions by revealing concrete forms of participative leadership implementation in school contexts and its impact on organizational work culture dynamics. A qualitative descriptive approach with case study design was employed, involving in-depth interviews with the school principal, teachers, and educational staff at SMKN 1 Agribisnis dan Agroteknologi Serui, Yapen Islands Regency, Papua. Data were collected through in-depth interviews, participatory observations, and documentary studies. Data validity was established through source and method triangulation as well as peer discussion. The interactive model of data analysis was applied, comprising data reduction, data display, and verification. The findings indicate that the school principal's participative leadership was manifested through school member involvement in program planning, decision-making, and school activity evaluation. This leadership implementation contributed to increased work motivation, sense of ownership toward the school, and the creation of a collaborative work climate. However, differences in readiness levels and participation among school members posed challenges to implementation. These findings affirm that the effectiveness of school principals' participative leadership requires strengthened communication and continuous development to be optimally implemented. The study extends participative leadership theory by demonstrating its viability in resource-constrained vocational education settings.